A supramolecular aluminium-based molecular catalyst for water oxidation into H2O2 in saline water. Issue 18 (16th August 2022) - Mathew, Siby; Sebastian, Abin; Kuttassery, Fazalurahman; Yamauchi, Yoshio; Isobe, Toshiaki; Hatanaka, Tsubasa; Funahashi, Yasuhiro; Tachibana, Hiroshi; Inoue, Haruo
Abstract : Capping TMβCD over AlTPyP has an excellent protective effect on seawater oxidation catalyzed by the supramolecular system AlTPyP@TMβCD against attack by Cl − . Abstract : Here, we report that an integrated supramolecular catalyst drives one-electron initiated two-electron water oxidation to form H2 O2 . The supramolecular catalyst was prepared by inclusion of pyridyl groups of 5, 10, 15, 20-tetra(4-pyridyl)porphyrinato-aluminium(iii ) (AlTPyP) within the cavity of heptakis(2, 3, 6-tri- O -methyl)-β-cyclodextrin (TMβCD). The supramolecular catalyst (AlTPyP@TMβCD) exhibited electrochemical one-electron initiated two-electron water oxidation even in saline water with high faradaic yield. On the other hand, bare AlTPyP without TMβCD suffered efficient electrochemical chlorination at the β-pyrrole position of the porphyrin ring predominantly forming tetra-chlorinated AlTPyPCl4 but the water oxidation was suppressed in the chloride-enriched environment. The crystal structure revealed the induced-fit-type encapsulation of AlTPyP within the cavity of TMβCD units, which well protected the catalyst from attack by chloride ions during the electrochemical water oxidation. The supramolecular approach would lead to a breakthrough concept for direct seawater oxidation.